A novel assay uncovers an unexpected role for SR-BI in LDL transcytosis. (2nd September 2015) - Armstrong, Susan M.; Sugiyama, Michael G.; Fung, Karen Y.Y.; Gao, Yizhuo; Wang, Changsen; Levy, Andrew S.; Azizi, Paymon; Roufaiel, Mark; Zhu, Su-Ning; Neculai, Dante; Yin, Charles; Bolz, Steffen-Sebastian; et al.
Abstract: Aims: Retention of low-density lipoprotein (LDL) cholesterol beneath the arterial endothelium initiates an inflammatory response culminating in atherosclerosis. Since the overlying endothelium is healthy and intact early on, it is likely that LDL passes through endothelial cells by transcytosis. However, technical challenges have made confirming this notion and elucidating the mechanisms of transcytosis difficult. We developed a novel assay for measuring LDL transcytosis in real time across coronary endothelial cell monolayers; we used this approach to identify the receptor involved. Methods and results: Murine aortas were perfused ex vivo with LDL and dextran of a smaller molecular radius. LDL (but not dextran) accumulated under the endothelium, indicating that LDL transcytosis occurs in intact vessels. We then confirmed that LDL transcytosis occurs in vitro using human coronary artery endothelial cells. An assay was developed to quantify transcytosis of DiI-LDL in real time using total internal reflection fluorescence microscopy. DiI-LDL transcytosis was inhibited by excess unlabelled LDL, while degradation of the LDL receptor by PCSK9 had no effect. Instead, LDL colocalized partially with the scavenger receptor SR-BI and overexpression of SR-BI increased LDL transcytosis; knockdown by siRNA significantly reduced it. Excess HDL, the canonical SR-BI ligand, significantly decreased LDL transcytosis. Aortas from SR-BI -deficient mice were perfused ex vivo with LDL and accumulated significantly less sub-endothelial LDL compared with wild-type littermates. Conclusion: We developed an assay to quantify LDL transcytosis across endothelial cells and discovered an unexpected role for SR-BI. Elucidating the mechanisms of LDL transcytosis may identify novel targets for the prevention or therapy of atherosclerosis.